Penggunaan Prinsip Kesantunan Berbahasa dalam Acara Talk Show Kick Andy Edisi “Keluargaku Kekuatanku” - Santi Aulia; Poppy Lutfiyani; Haerul Tamimi (Jurnal Syntax Transformation, 2021)
This study aims to discuss the principle of politeness that exists in the Kick Andy Talk Show "My Family My Strength" edition. The method in this research is descriptive-qualitative. The results of this study indicate that the principle of politeness will be used by the talk show host to the speakers as well as vice versa. As in the Kick Andy Talk Show, Andy as the master of ceremonies will use the principle of politeness to his speakers and even the source will use the principle of politeness